New perspective on ECE mechanism of monohydroxycinnamic acid oxidation with carbon nanotube electrode. (1st November 2020) - Wada, Ryotaro; Takahashi, Shota; Muguruma, Hitoshi
Highlights: ECE mechanism of monohydroxycinnamic acid oxidation is presented. A carbon nanotube-carboxymethylcellulose electrode is used. Proposed mechanism is confirmed by simulations using DigiElch software. Monohydroxycinnamic acids are converted into dihydroxycinnamic acids. Abstract: In this study, the electrochemical-chemical-electrochemical (ECE) mechanism of monohydroxycinnamic (ferulic, sinapic, and p-coumaric) acid oxidation is presented from a new perspective. Successful mechanistic interpretation employs a carbon nanotube (CNT)-carboxymethylcellulose (CMC) electrode, which exhibits distinctive ECE behavior in cyclic voltammetry (CV), unlike other electrodes. The proposed mechanism is confirmed by simulations using DigiElch software. Monohydroxycinnamic acids are oxidized by an EECE mechanism (Er Er Ci Er  = A ⇄ B + e − ; B ⇄ C + e − ; C ⇄ D; D + 2e − ⇄ E). The first electrochemical step (Er Er ) comprises two consecutive oxidations (A ⇄ B + e − ; B ⇄ C + e − ), which appear as separate anodic peaks. The reaction at the less positive potential involves oxidation of the hydroxyl group to a phenoxy radical (B), which exists in three mesomeric forms that are oxidized in the second reaction to cations (C) that undergo hydrolysis to their respective o-quinones (D). The hydrolysis reaction (C → D) exhibits a large rate constant and occurs rapidly on the voltammetric time scale. Thus, the overall Er Er Ci process appears to be chemically irreversible. Finally, the monohydroxycinnamic acids are converted into dihydroxycinnamic acids (caffeic or 5-hydroxyferulic acids), which condense into a reversible, two-electron catechol/o-quinone redox system (D + 2e − ⇄ E). Electrochemical quantitation is based on the proportionality of the peak currents to the monohydroxycinnamic acid concentration. The voltammetrically determined monohydroxycinnamic acid content in real food samples agrees with the high-performance liquid chromatography results. The CNT-CMC electrode extends fundamental studies of the ECE mechanism to systems that cannot be examined using conventional electrodes, thereby demonstrating its utility in electrochemical studies. Graphical abstract: Image, graphical abstract